Biointegrated and Wirelessly Powered Implantable Brain Devices: A Review - Das, Rupam; Moradi, Farshad; Heidari, Hadi (IEEE transactions on biomedical circuits and systems, 2020)
Implantable neural interfacing devices have added significantly to neural engineering by introducing the low-frequency oscillations of small populations of neurons known as local field potential as well as high-frequency action potentials of individual neurons. Regardless of the astounding progression as of late, conventional neural modulating system is still incapable to achieve the desired chronic in vivo implantation. The real constraint emerges from mechanical and physical differences between implants and brain tissue that initiates an inflammatory reaction and glial scar formation that reduces the recording and stimulation quality. Furthermore, traditional strategies consisting of rigid and tethered neural devices cause substantial tissue damage and impede the natural behavior of an animal, thus hindering chronic in vivo measurements. Therefore, enabling fully implantable neural devices requires biocompatibility, wireless power/data capability, biointegration using thin and flexible electronics, and chronic recording properties. This article reviews biocompatibility and design approaches for developing biointegrated and wirelessly powered implantable neural devices in animals aimed at long-term neural interfacing and outlines current challenges toward developing the next generation of implantable neural devices.